Health, Disasters and Risk - ISDR (2008)
Trata de Health, Disasters and Risk.
1.health and disaster risk 2.climate change effects on health 3mitigation and preparedness
incluye índice
Col. Agro
Keywords: 1.MENTAL HEALTH 2.PUBLIC HEALTH 3. GENDER AND HEALTH